Effect of high-Z dopant on the laser-driven ablative Richtmyer–Meshkov instability. (15th May 2017) - Xu, B.; Ma, Y.; Yang, X.; Tang, W.; Wang, S.; Ge, Z.; Zhao, Y.; Ke, Y.
Abstract: The effects of high- Z dopant on the laser-driven ablative Richtmyer–Meshkov instability (RMI) are investigated by theoretical analysis and radiation hydrodynamics simulations. It is found that the oscillation amplitude of ablative RMI depends on the ablation velocity, the blow-off plasma velocity and the post-shock sound speed. Owing to enhancing the radiation at the plasma corona and increasing the radiation temperature at the ablation front, the high- Z dopant in plastic target can significantly increase the ablation velocity and the blow-off plasma velocity, leading to an increase in oscillation frequency and a reduction in oscillation amplitude of the ablative RMI. The high- Z dopant in plastic target is beneficial to reduce the seed of ablative Rayleigh–Taylor instability. These results are helpful for the design of direct drive inertial confinement fusion capsules.